REFORMASI MANAJEMEN KELEMBAGAAN DAN KURIKULUM PENDIDIKAN MUHAMMAD ABDUH DI MESIR - Samsul Bahri; Erni Qomariyah (Halu Oleo University, 2023)
The research aimed to understand the reforms implemented by Muhammad Abduh in Egypt and to analyze the restructuring of institutional management and curriculum he conducted. The research methodology was a literature review with content analysis to reveal Muhammad Abduh's thoughts related to his mission. The findings indicate that Abduh's thoughts significantly influenced the modernization of Islamic education, particularly at al-Azhar University. He stressed the need to integrate modern sciences and technology with Islamic teachings. These reforms were intended to strengthen Islam's position amidst the advancement of science and modernization challenges.